Makna Denotatif dan Konotatif dalam Novel Bulan Karya Tere Liye : Kajian Semantik - Kartika Auliyah (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2026)
Semantics is a discipline of linguistics that deeply examines the meaning of words, encompassing the origins of their formation, the process of evolution, and the historical factors that trigger shifts in meaning within a language. In semantic studies, a fundamental distinction is made between denotative meaning, which refers to the literal or actual meaning, and connotative meaning, which carries emotional value or a non-actual, figurative sense. This research focuses on analyzing the variation of both types of meaning in Tere Liye's novel Bulan, with the main objective of comprehensively describing the manifestation of denotative and connotative expressions. The method used is qualitative with a descriptive approach, where the researcher acts as the key instrument (human instrument). This method is also known as the naturalistic approach, as data collection takes place under natural object conditions, with data analysis heavily emphasizing the in-depth qualitative aspects. The results of the study indicate that the use of denotative meaning has a much more dominant frequency than connotative meaning. This dominance occurs because the majority of the narrative in the novel tends to utilize the actual, lexical meaning. This signals the author’s (Tere Liye’s) intention to present the adventure story with straightforward and transparent language, allowing the reader to easily comprehend the storyline without being hindered by the complexity of figurative meaning interpretation.